(untitled) (diségno, 2025)
This research explores how drawing and tracing have evolved into critical tools in scientific and political discourse. Tracing, once seen as mere reproduction, now involves transferring conditions, engaging with past events, and addressing urgent issues –particularly within forensic aesthetics. The study questions the epistemological status of traces, framing them as ontologically significant in both artistic and technical production. Drawing is approached as a performative act that reveals unsensed or unconscious micro-events. It extends beyond the body. The research aims to conceptualize how tracing and drawing converge through the re-visualization of invisible. The political agency of drawing and its dialogical potential between abstraction and grounded realities. Simultaneously, it considers the aesthetic and technical dimensions of drawing as a dynamic, non-standard process. Tracing is redefined as performative –through choreography, erasure and evolving imagery– opening new paths for engaging space, perception and meaning.